2010
DOI: 10.3382/ps.2009-00424
|View full text |Cite
|
Sign up to set email alerts
|

Detection and molecular characterization of enteric viruses from poult enteritis syndrome in turkeys

Abstract: This study was conducted to detect and characterize enteric viruses [rotavirus, turkey astrovirus-2 (TAstV-2), reovirus, and turkey coronavirus] from cases of poult enteritis syndrome (PES) in Minnesota turkeys. Of the intestinal contents collected from 43 PES cases, 25 were positive for rotavirus and 13 for small round viruses by electron microscopy (EM). Of the enteric virus-positive cases by EM (n=27), 16 cases had rotavirus or small round viruses alone and the remaining 11 cases had both viruses. None of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
66
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(73 citation statements)
references
References 31 publications
6
66
0
1
Order By: Relevance
“…Results obtained in this study showed that viral excretion from infected turkeys can persist for a much longer period than the manifestation of clinical signs. Although during natural infections in the field prolonged detection of viruses in the faeces can also be due to transmission of the virus among birds, this finding is consistent with field data obtained from several studies in turkeys where TAstV2 was detected in birds up until 9 to 12 weeks of age (Pantin-Jackwood et al, 2007;Canelli et al, 2009;Jindal et al, 2010b), The prolonged cloacal shedding could also explain cases of RT-PCR astrovirus-positive flocks detected in the absence of clinical signs (Pantin-Jackwood et al, 2008b;Domanska-Blicharz et al, 2011) and should be considered a confounding factor from a diagnostic point of view. In combination with the well-known high environmental resistance of astroviruses (Schultz-Cherry …”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Results obtained in this study showed that viral excretion from infected turkeys can persist for a much longer period than the manifestation of clinical signs. Although during natural infections in the field prolonged detection of viruses in the faeces can also be due to transmission of the virus among birds, this finding is consistent with field data obtained from several studies in turkeys where TAstV2 was detected in birds up until 9 to 12 weeks of age (Pantin-Jackwood et al, 2007;Canelli et al, 2009;Jindal et al, 2010b), The prolonged cloacal shedding could also explain cases of RT-PCR astrovirus-positive flocks detected in the absence of clinical signs (Pantin-Jackwood et al, 2008b;Domanska-Blicharz et al, 2011) and should be considered a confounding factor from a diagnostic point of view. In combination with the well-known high environmental resistance of astroviruses (Schultz-Cherry …”
Section: Discussionsupporting
confidence: 80%
“…A genetically and antigenically distinct type of turkey astrovirus was then identified in 1996 (Turkey astrovirus type 2 [TAstV2]) by Koci et al (2000a). Since these first detections, enteritis in turkey has been increasingly associated with the presence of astroviruses (Cattoli et al, 2007;Pantin-Jackwood et al, 2007, 2008aDa Silva et al, 2008;Jindal et al, 2010a), although high astrovirus prevalence has also been reported in apparently healthy turkey flocks (PantinJackwood et al, 2007(PantinJackwood et al, , 2008aJindal et al, 2010b;Domanska-Blicharz et al, 2011). TAstV2 appears to be the most common among the identified turkey astroviruses, while TAstV1 and avian nephritis virus* an astrovirus first described as responsible for nephritis in chicken (Imada et al, 2000)*have only been detected sporadically in turkey flocks (Pantin-Jackwood et al, 2007, 2008aDomanska-Blicharz et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, another report showed that reovirus strains isolated from turkeys and chickens with tenosynovitis/arthritis did not induce tenosynovitis/arthritis when inoculated into footpads of 1-day-old poults (Afaleq & Jones, 1989). There are no recent (<20 years) reports of lameness associated with turkey reovirus, although turkey enteric reovirus (TERV) has been identified as a cause of diarrhoea, poult enteritis and light turkey syndrome in turkeys (Jindal et al, 2010;Mor et al, 2013a).…”
Section: Viral Tenosynovitis/arthritis Was First Reported In 1968 Inmentioning
confidence: 97%
“…In the field, rotaviruses are commonly detected via molecular methods, however, the situation is complicated by the fact that rotaviruses (and other co-infecting viruses) are often found in healthy flocks, exhibiting no enteric disease signs (Jindal et al 2009, Jindal et al 2012, Day et al 2013. Some reports demonstrating the presence of this virus in healthy flocks of commercial chickens are available (Pantin-Jackwood et al 2007, Pantin-Jackwood et al 2008, Jindal et al 2010). Due to rotavirus features of high particle elimination by infected hosts (Koopmans & Duizer 2004) and resistance to environmental conditions (Harakeh & Butler 1984), coupled with the density of flocks, the conditions for transmission of virus are increased.…”
Section: Discussionmentioning
confidence: 99%